Reincarnation in Plato and in the Christian Perspective - Mantzanas, Michail (Peitho. Examina Antiqua, 2015)
The present study focuses on research about reincarnation in order to formulate some preliminary conclusions concerning various philosophical theories. The overview extends over a considerable period range, from ancient Greek and up to the patristic tradition. The relevant issues include the problem of evil, the question of human decomposition and death as well as reincarnation (metempsychosis) in the Platonic thought. The problem of evil is a problem of reason that emerges from the philosophical background of ancient Greek thought but also from the subsequent Christian patristic thought and transforms itself into diverse concepts (e.g. the significance of justice). According to the original thought of Socrates, evil is associated with ignorance and good with knowledge. This point of view is given a brief review in the philosophical thought of several important representatives of the patristic tradition (e.g., Origen and Gregory of Nyssa). On the other hand, the idea of immortality of the soul, which dates to the religious movement of the Orphic mysteries (seventh century BC) means that the persistence of the immortal soul at the moment of death needs the use of a new body. This essay will try to analyze the ancient character of the myth of reincarnation through the perspectives of philosophy and religion.